Falsafah Manusia dan Individu dalam Novel Rinai Kabut Singgalang Karya Muhammad Subhan : Falsafah Manusia dan Individu dalam Novel Rinai Kabut Singgalang Karya Muhammad Subhan - Dara Puspa Mulyana Mulyana (Signifiѐ, 2023)
Human and Individual Philosopy is used as a way of life as well as a source of lessons derived from nature for the survival of the Minangkabau people. This study aims to determine the Human and Individual Philosopy in Muhammad Subhan's Novel Rinai Fog Singgalang. The research method uses descriptive analysis method. The results of the research Human and Individual Philosopy in Muhammad Subhan's Rinai Fog Singgalang Novel after being xamined through the building blocks of literary works, it can be concluded that there are nine human and individual data.